Prevalence and acceptance of therapy with medical compression stockings - Pannier, F.; Hoffmann, B.; Stang, A.; Jöckel, K.-H.; Rabe, E. (Phlebologie, 2007)
The aim of this study was to assess the prevalence of use of medical compression stockings (MCS) in the general adult population in Germany, to comment the indications for which MCS therapy has been described and the patients’ experience with it. Methods: The survey is based on the Bonn Vein Study. The population of this cross-sectional study was randomly recruited between November 2000 and March 2002 from the registers of residents of the city of Bonn and two rural townships in the area. In total, 3.072 men and women were included in the trial. In addition to clinical examination and duplex-ultrasound, participants were asked whether any phlebological treatment had been carried out due to a leg disorder or disease.. If compression stockings had been worn, we asked for details such as compression class and length of stockings, wearing time, effectiveness, and recognition. Results: In total, 22.9% of people providing information (12.7% of male, 31.0% of female) mentioned having received a specific phlebological treatment in the past. Therapy with compression stockings had the highest prevalence with 14.6% in the general population (7.5% of males, 20.3% of females). The mean age at the first prescription was 45.5 years (SD = 14.3 years). With increasing severity of venous disease, as rated according to the CEAP classification, the prevalence increased from 1% in C0 patients to 82% in C5/C6 patients. Of 450 participants who had used compression stockings in the past, 309 (68.6%) did not wear CS at the time of the survey. The remainder had generally been wearing them on five or more days per week (73.0%) for 8 or more hours per day (89.4%). On average, 71.3% of the participants said that the disease for which MCS were prescribed, had improved as a result of MCS therapy. Improvement concerned a reduction of sensations of swelling (84.2%), of heaviness (89.4%), leg pain after long periods of standing (60.9), and tension in the legs (78.9).
Keywords: Medical compression stockings; Bonn vein study; CEAP; chronic venous disorders